The Impact of Waqf Core Principles on Enhancing Waqf Asset Collection and Safeguarding Strategies - Raji Reza Ilahi; Dede Haris Sumarno; Kartini Kartini (Badan Wakaf Indonesia, 2026)
This study examines the influence of governance based on Waqf Core Principles (WCP) on improving waqf fundraising strategies and safeguarding waqf assets. Despite Indonesia’s significant waqf potential, weak governance, limited accountability, and inadequate asset protection continue to undermine public trust and fundraising performance. Employing a qualitative normative approach, this study analyzes regulatory frameworks, scholarly literature, and WCP as an international governance standard for waqf institutions. The findings reveal that WCP-based governance enhances institutional credibility, strengthens public trust, improves strategic fundraising, and reinforces legal and managerial protection of waqf assets. This study concludes that WCP constitutes a strategic governance instrument for sustainable waqf management and recommends its institutionalization within national waqf governance policies.